Analyzing & Evaluating The Traffic Performance For Urban streets Network Using (Highway Capacity Manual) HCM2016 - أكرم رستم,; أحمد موسى, (Latakia University Journal -Engineering Sciences Series, 2022)
This study presents an assessment of the traffic flow on the urban arteries, which can be considered as main linking axes of the movement between the main areas and the outskirts of the city center. Therefore, improving the traffic situation on these arteries will have a significant impact on improving performance on these axes and reduce time losses, it can also have important environmental repercussions such as reducing the emission of pollutants and reducing noise which is caused by traffic movements. The significant increase in the number of road transport that have introduced to the country in recent years has led to an increase in the abundance of traffic on the roads and streets, as well as to an increase in the number of traffic accidents and delay times, in addition to a decrease in speeds, especially on the main roads in city centers, and thus appeared The need to study and analyze the traffic movement on those roads in order to organize and control the traffic process on them, to ensure the safety and ease of movement The traffic study was conducted on a network of main streets in the city Lattakia to determine the level of services for these streets in accordance with the standards of the (highway capacity manual HCM2016). In this study, it's proposed to develop these standard in a way that suits the engineering and traffic reality of those arteries with the local conditions of Syrian cities by introducing the effect of the secondary roads and side movement, which constitute a large part of the movement on these axes, which the aim of develop them and to serve the high traffic volume between the active centers in city.